Capability gap in relation to public relations´ strategic issues in Latin America - Sadi, Gabriel; Álvarez-Nobell, Alejandro (Elsevier, 2024)
This study explores an area that has not been widely researched in the Latin American and Caribbean region: the identification of a capability gap in relation to key strategic public relations and communication management issues and activities. To this end, this article presents findings and analysis from a survey conducted in 20 Latin American and Caribbean countries in 2020. The existence of a capability gap in relation to key issues and activities in public relations and communication management is confirmed, which represents a challenge for the development of the public relations field as well as for higher education institutions across the region.
Keywords: Relaciones públicas - América latina; Relaciones públicas - Caribe (Región); Comunicación en la gestión; Universidades; Comunicación; Public relations; Capabilities; Strategic issues; Latin America; The Caribbean